HEAT TREATMENT EFFECT ON MECHANICAL PROPERTIES OF JIS SCM4 STEEL - Hestiawan, Hendri; Zuliantoni, Zuliantoni; Febriyanto, Dwi (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2019)
It is about steel JIS SCM4 of 0.39% C, 0.28% Si, 0.77% Mn, 0.95% Cr and 0.17% Mo composition. The steel was heated to improve the mechanical properties. The heat treatment was applied on  a cylindrical specimens of 20 mm diameter at 850 C for 30 minutes. The heated samples were then quenched into media of oil, coconut oil, kerosene, water and the other was annealed. The quenched specimens were tempered at 300 °C for 30 minutes. Testing of mechanical properties was tensile and hardness tests. The lower viscosity of the quenchant gave the tensile stress and hardness higher. The highest one  was about 1779 MPa and 52 HRC of specimens quenched to water and  the highest strain was achieved as high as to 21.76% of the annealed one. The microstructure of the  quench-temper was martensitic phase, and ferritic-pearlitic of the annealed.